Does ageing aggravate parkinsonian disability? - Blin, J (1991)
The influence of age of onset of Parkinson's disease on the severity and the pattern of motor symptoms was investigated by comparing the motor scores with and without levodopa therapy in two groups of patients divided according to age of onset (early less than 50, late greater than 60 years) and matched for disease duration (n = 69 in each group, Study I). The baseline score, that is, the motor disability of patients when off levodopa, was similar in the early- and late- onset groups. In contrast, the residual motor score, assessed when the effect of levodopa treatment was maximum and stable, was significantly higher in the late onset group. When the two groups of patients were matched, in addition, for their residual motor score, (n = 54 in each group, Study II), no difference was observed between the early and late onset groups, except for gait disorder which was more severe in older patients. These results suggest that age of onset mainly affects the response to levodopa therapy, because it may increase the prevalence of non-dopaminergic lesions of the brain, including those responsible for gait disorders.